Facing The Times: Challenges Of Indonesia's Goverment System In The Modern Era - Aziza, Soba Bayinanor; Slam, Zaenul (Current Issues on Elementary Education Journal, 2025)
In this rapidly evolving modern era, the Indonesian government faces various challenges that can affect the quality and effectiveness of national governance. The purpose of this article is to identify and analyze five major issues challenging Indonesia's governmental system. These include digitalization and technology, transparency and accountability, corruption and integrity of state apparatus, public participation and substantive democracy, and social and technological complexity. Through a descriptive approach and evidence-based analysis using scholarly references, this article concludes that although progress has been made in various aspects of governance, many obstacles remain to be overcome to create a better governance system. Amid the challenges of digitalization and technology, transparency and accountability remain issues in data management and information protection, demanding equitable infrastructure and equal access across Indonesia. Despite reforms, anti-corruption efforts need to be strengthened through stricter oversight. Meanwhile, substantive democracy and public participation require increased political awareness and the use of technology to enhance civic engagement. Lastly, technological complexity and social diversity highlight the need for the Indonesian government to keep pace with technological advancements and social pluralism.